Imbuing medical professionalism in relation to safety: a study protocol for a mixed-methods intervention focused on trialling an embedded learning approach that centres on the use of a custom designed board game. Issue 7 (17th July 2017) - Ward, Marie; McAuliffe, Eilish; Ní Shé, Éidín; Duffy, Ann; Geary, Una; Cunningham, Una; Holland, Catherine; McDonald, Nick; Egan, Karen; Korpos, Christian
Abstract : Introduction: Healthcare organisations have a responsibility for ensuring that the governance of workplace settings creates a culture that supports good professional practice. Encouraging such a culture needs to start from an understanding of the factors that make it difficult for health professionals to raise issues of concern in relation to patient safety. The focus of this study is to determine whether a customised education intervention, developed as part of the study, with interns and senior house officers (SHOs) can imbue a culture of medical professionalism in relation to patient safety and support junior doctors to raise issues of concern, while shaping a culture of responsiveness and learning. Methods and analysis: We will use quantitative and qualitative methods to collect data. The sample size will be approximately 200 interns and SHOs across the two hospital sites. Two surveys will be included with one measuring leadership inclusiveness and psychological safety and a second capturing information on safety concerns that participants may have witnessed in their places of work. The PlayDecide embedded learning intervention will be developed with key stakeholders. This will be trialled in the middle stage of data collection for both interns and SHOs. A detailed content analysis will be conducted on the surveys to assess any changes in reporting following the PlayDecide intervention. This will be compared with the incident reporting levels and the results of the preintervention and postintervention leadership inclusiveness and psychological safety survey. Statistical analysis will be conducted using SPSS. Differences will be considered statistically significant at p<0.05. Semistructured interviews using a critical incident technique will be used for the ongoing analysis and evaluation of the project. These will be transcribed, de-identified and coded into themes. Ethics and dissemination: The study has been granted ethics approval from University College Dublin (Ref. LS-15–19-Ward-McAuliffe: Imbuing Medical Professionalism in Relation to Safety). The study results will be disseminated through peer-reviewed publications.